2001
DOI: 10.1063/1.1376407
|View full text |Cite
|
Sign up to set email alerts
|

Doping-induced losses in AlAs/GaAs distributed Bragg reflectors

Abstract: We have studied n- and p-type doping-induced performance degradation of AlAs/GaAs distributed Bragg reflectors (DBRs) for applications in vertical cavity lasers (VCLs). Based on high-accuracy optical reflectance and triple-axis x-ray diffraction measurements on a variety of differently doped DBR structures grown by metalorganic vapor-phase epitaxy, a fitting procedure was employed to extract the doping-dependent optical loss. A striking observation is that the reflectance of these DBRs is much more sensitive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
12
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 32 publications
2
12
0
1
Order By: Relevance
“…Another important issue concerns the cavity losses related to the doping of the DBRs [15]. To estimate the influence of doping on the photon confinement, we have fabricated a similar undoped microcavity structure, and compared the FWHM linewidths of the cavity modes in the two samples.…”
Section: Methodsmentioning
confidence: 99%
“…Another important issue concerns the cavity losses related to the doping of the DBRs [15]. To estimate the influence of doping on the photon confinement, we have fabricated a similar undoped microcavity structure, and compared the FWHM linewidths of the cavity modes in the two samples.…”
Section: Methodsmentioning
confidence: 99%
“…Instead we suggest, as already discussed in Ref. 3, that the reduced reflectance is due to an inhomogeneous interdiffusion process resulting in interface roughening and increased scattering loss. 3 It should be noted that the topmost GaAs surface of the DBRs after cooling down in AsH 3 ambient remains smooth, indicating that the interface roughness of the DBRs should not influence the quality of the QWs grown upon them.…”
mentioning
confidence: 92%
“…By contrast, there have been reports on improved VC-SEL performance from the use of an undoped bottom DBR, 2 and in a previous study, we showed that AlAs/ GaAs DBR properties are effectively more degraded by n-type rather than p-type doping. 3 Based on detailed investigations of doping and annealing dependent x-ray diffraction ͑XRD͒ and reflectance measurements, it was argued that this degradation is due to n-type doping-enhanced Al-Ga interdiffusion effects resulting in increased interface scattering. 3 More recently, Haberland et al used reflectance spectroscopy to measure the development of interface roughness in situ during the metal-organic vapor-phase epitaxy ͑MOVPE͒ growth of a 650 nm VCSEL structure.…”
mentioning
confidence: 99%
See 2 more Smart Citations